Meningkatkan Nilai IQ melalui Penerapan Story-telling dalam Pengajaran Kristen: Kajian Berbasis Daniel 1:8-20 - Leiwakabessy, Tabita; Purwonugroho, Daniel Pesah; Suseno, Aji (Jurnal Lentera Nusantara, 2024)
Intellectual intelligence is essential for the development of learners. Success in problem-solving, analysis, reasoning, and application demonstrates the competence of learners in enhancing aspects of IQ intelligence. IQ is highly dependent on the learning materials. The interaction in communicating learning materials varies greatly depending on the teacher's ability to choose appropriate teaching methods to achieve optimal learning outcomes. Storytelling is chosen as a teaching method to stimulate the IQ values of learners. The teaching materials in storytelling are also designed to bring benefits to learners. From a Christian perspective, the story of Daniel can lead learners to experience intellectual intelligence. Daniel's obedience to God gives him high intelligence because of God's grace. Through storytelling based on the story of Daniel, learners can emulate Daniel's obedience to God. With a descriptive qualitative approach, it can be concluded that storytelling of the Daniel 1:8-20 story can enhance the IQ scores of learners.AbstrakKecerdasan intelektual dibutuhkan untuk mengembangkan diri peserta didik. Keberhasilan memecahkan masalah, menganalisa, menalar dan mengaplikasikan membuktikan kompetensi peserta didik mampu meningkatkan aspek kecerdasan IQ. IQ sangat bergantung dengan mater pembelajaran. Interaksi dalam mengkomunikasikan materi pembelajaran sangat bervariasi tergantung kemampuan guru dalam memilih metode mengajar yang sesuai agar dapat meraih hasil belajar yang maksimal. Story-telling dipilih sebagai metode mengajar untuk merangsang nilai IQ peserta didik. Bahan ajar dalam story-telling juga di desain agar dapat membawa manfaat kepada peserta didik. Dalam perspektif Kristen, kisah tentang Daniel dapat membawa peserta didik mengalami kecerdasan intelektual. Ketaatan Daniel kepada Allah membuat Daniel memiliki kemampuan intelegensi yang tinggi karena anugerah Allah. Dengan story-telling berbasis kisah Daniel, maka peserta didik dapat meneladani ketaatan Daniel kepada Allah. Dengan pendekatan kualitatif deskriptif, dapat disimpulkan bahwa story-telling kisah Daniel 1:8-20 dapat meningkatkan nilai IQ peserta didik.